Crowdsourcing approaches for knowledge organization systems: crowd collaboration or crowd work? - Maayan Zhitomirsky-Geffet; Barbara H. Kwasnik; Julia Bullard; Lala Hajibayova; Juho Hamari; Timothy Bowman (Copenhagen, 2025)
Development of Internet technologies has empowered ordinary users to create, contribute, share and connect with other members of the community. As users learn to exploit the potential of networked communications, they participate in a process, which facilitates a shift from individual to collective contributions and introduces an opportunity for multi-vocal and multi-faceted representation of cultural heritage. Open access to crowdsourced collections requires reconsideration of the traditional authoritative approach of cultural heritage institutions. The arduous nature of the work rendered voluntarily in cultural heritage crowdsourcing initiatives calls for reconsideration of power relationships and giving power to devoted contributors supported by modern “intelligent” technology to regulate the process of representation and organization. Taking into consideration the fact that crowdsourced data are not without flaws, the question is how to better utilize the collective intelligence to create quality information. In this context, various issues such as power, control, trust, inter-contributor consensus, heterogeneity of opinions will be raised and discussed by the panelists. Each of the panelists comes from a different field of expertise (Computer science, Information science, Economics, Communication studies, cultural heritage) and various cultural backgrounds and geographical locations (United States, Europe and Israel). This diversity will be reflected in the presented perspectives on the crowdsourcing topic.
Proceedings of the Association for Information Science and Technology